Os impactos da implementação do LEMAT na UFPA campus de Abaetetuba, numa perspectiva passado presente e futuro - SANTOS, Fabiana Sardinha dos (2022)
For many years the subject of Mathematics was seen as a difficult subject, the difficulties were observed in students from basic education to higher education and to remedy these learning difficulties in higher education and further train students, it emerged on the Abaetetuba campus o Laboratory of Ethnomathematics of the Amazon Tocantina-LEMAT. Within this perspective, we will learn about the actions, events and support and support projects offered by this laboratory, which aims to highlight the local culture and support and encourage students during graduation and for continuing education. Still in this research, we will diagnose which difficulties undergraduate students face, especially those who reside in another municipality, and how the educational institution and LEMAT have interfered to alleviate them.